Ranking Family Role Models Shaping Adolescent Decision-Making - Soares Vaneli , Gisela; Daun Crudo , Micaela; Del Croce , Paolo (Journal of Psychosociological Research in Family and Culture, 2025)
Objective: This study aimed to identify and rank the most influential family role models that shape adolescents’ decision-making processes through an integrated qualitative–quantitative research approach. Methods and Materials: The research employed a sequential mixed-method design. In the first phase, a qualitative literature-based analysis was conducted until theoretical saturation was achieved. Using NVivo 14, eight major themes were identified, representing the primary family role models influencing adolescents’ decision-making: parental modeling, sibling influence, grandparental wisdom, extended family role models, parental communication style, family values and beliefs, family decision climate, and socioeconomic context. In the second phase, a quantitative ranking survey was administered to 200 adolescents in Italy, who evaluated the importance of each theme using a 5-point Likert scale. Data were analyzed with SPSS 26 using descriptive statistics, Friedman’s test, and Kendall’s W to assess agreement among participants. Findings: The analysis revealed significant differences among the ranked family role model themes (p < 0.001). Parental modeling received the highest mean score (M = 4.72, SD = 0.41), followed by parental communication style (M = 4.58) and family values and beliefs (M = 4.39). Socioeconomic and environmental context ranked lowest (M = 3.48). Kendall’s W coefficient of 0.84 indicated a high level of consensus among participants regarding the hierarchy of family influences. Conclusion: The study concludes that family influence on adolescent decision-making is primarily shaped by direct behavioral and emotional modeling within supportive, communicative, and value-oriented households. Strengthening family dynamics through targeted mentoring and communication-focused interventions may enhance adolescents’ decision-making competence and moral reasoning.